Effect of Brand Image, the Quality and Price on Customer Satisfaction and Implications for Customer Loyalty PT Strait Liner Express in Jakarta - Subaebasni, Subaebasni; Risnawaty, Henny; Wicaksono, A.R. Arie (International Review of Management and Marketing, 2019)
The purpose of this study was to determine the effect of brand image, service quality and price both partially and simultaneously to the customer satisfaction and the impact of customer satisfaction on customer loyalty. Using quantitative research methods, with a sample of 171 respondents. Data were analyzed using Structural Equation Modeling (SEM). The results of the analysis showed that the partial towards customer satisfaction, the brand image variable has a positive and significant impact with a coefficient of 0.773. Variable quality of service has a positive and significant impact with a coefficient of 0.720, the price variable price has a positive and significant impact with a coefficient of 0.683. In partial variable customer satisfaction with loyalty has a positive and significant impact with a coefficient of 0.602. The results of the analysis showed that simultaneous independent variables to customer satisfaction positively and significantly with a coefficient of 0.720. The results of the analysis showed that the partial loyalty, brand image variable has a positive and significant impact with a coefficient of 0.672. Variable quality of service has a positive and significant impact with a coefficient of 0.739, the price variable price has a positive and significant impact with a coefficient of 0.739. The results of the analysis showed that simultaneous independent variables loyalty, positive and significant impact with a coefficient of 0.734. Keywords: Influence of Brand Image, Quality Service, Price, Customer Satisfaction and Customer Loyalty JEL Classifications: M21, M31, Z33 https://doi.org/10.32479/irmm.7440